Kajian Bioarkeologi: Osteobiografi Temuan R.PNY (PULAKI) di Situs Pulaki, Kecamatan Gerokgak, Kabupaten Buleleng - Maulana, Adzmi Akbar; Agung Bawono, Rochtri; Srijaya, I Wayan (Humanis; Vol 26 No 3 (2022), 2022)
Bioarchaeology is the science that covers the relationship between bioanthropology and archaeology to reconstructing biological and cultural processes in the past. The study focuses on skeletal components of R.PNY (PULAKI) on Pulaki Site that aim to learn information about human osteobigraphy. In this study, authors use methods of data-collection of library studies, obsevations, and interviews. Data is then treated using macroscopic analysis, microscopic analysis, anthropogenic analysis, anthropometrics analysis and comparative analysis. Forensic theory is used to assist in the process of analysis. By the process of identification it is known that the R.PNY (PULAKI) skeleton has an unidentified gender of about 6-12 years of age with a height of 125.102 cm ± 10 cm by length of bone. In addition, there are indications of pathology and bone modification such as dental hypoplasia, caries occlusal, bone fracture, bone modification by physical agents, and bone modification by nonhuman biological agents.